Recent Advances in the Composition and Heterogeneity of the Arabidopsis Mitochondrial Proteome - Lee, Chun Pong; Taylor, Nicolas L.; Millar, A. H. (Frontiers in Plant Science, 2013)
Mitochondria are important organelles for providing the ATP and carbon skeletons required to sustain cell growth. While these organelles also participate in other key metabolic functions across species, they have a specialized role in plants of optimizing photosynthesis through participating in photorespiration. It is therefore critical to map the protein composition of mitochondria in plants to gain a better understanding of their regulation and define the uniqueness of their metabolic networks. To date, less than 30% of the predicted number of mitochondrial proteins has been verified experimentally by proteomics and/or GFP localization studies. In this mini-review, we will provide an overview of the advances in mitochondrial proteomics in the model plant Arabidopsis thaliana over the past five years. The ultimate goal of mapping the mitochondrial proteome in Arabidopsis is to discover novel mitochondrial components that are critical during development in plants as well as genes involved in developmental abnormalities, such as those implicated in mitochondrial-linked cytoplasmic male sterility.